The Long-Term Effects of Capital Requirements - Gianni De Nicolò; Nataliya Klimenko; Sebastian Pfeil; Jean-Charles Rochet (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We build a stylized dynamic general equilibrium model with financial frictions to analyze costs and benefits of capital requirements in the short-term and long-term. We show that since increasing capital requirements limits the aggregate loan supply, the equilibrium loan rate spread increases, which raises bank profitability and the market-to-book value of bank capital. Hence, banks build up larger capital buffers which (i) lowers the public losses in case of a systemic crisis and (ii) restores the banking sector's lending capacity after the short-term credit crunch induced by tighter regulation. We confirm our model's dynamic implications in a panel VAR estimation, which suggests that bank lending has even increased in the long-run after the implementation of Basel III capital regulation.
Keywords: E21; E32; F44; G21; G28; 330; bank capital requirements; credit crunch; systemic risk